Washington Crossing the Media: American Presidential Rhetoric and Cultural Iconography - Jutta Ernst (European Journal of American Studies)
The Revolutionary War has been of prime importance to American self-perceptions and to the formation of its national identity. As a foundational moment with a strong mythical dimension it has become a cherished point of reference for the nation’s leaders, who, in their speeches and written communications, rely on the most widely accepted cultural iconography to recall this event. A time-honored, traditional discourse might, however, go together with the use of contemporary media technology as a means of distribution, as in the case of Barack Obama. Framing Obama’s rhetorical strategies within 19th- and 20th-century artistic representations of one specific historical moment from the Revolutionary War, Washington’s crossing of the Delaware river, this paper seeks to contribute to an enlarged understanding of the intricate relations between politics, the arts, and media development and of the ways they appropriate the past